Exploring elementary teacher education students’ perception on parental involvement - Yosef Yosef; Fadhlina Rozzaqyah (International Journal of Evaluation and Research in Education (IJERE), 2024)
This study concerned with elementary teacher education students not prepared to have competency in parental involvement in education. The research aimed to explore their perceptions of the importance of parental involvement in elementary education. A 30-item online survey questionnaire, which employed a series of Likert-style statements in five types of parent involvement, was utilized to measure their perceptions. The study involved 1,459 undergraduate students majoring in elementary teacher education as participants, representing 72 study programs of universities and college schools in Indonesia. Descriptive and mean score comparison analyses were employed to make the obtained data meaningful. The finding revealed that the students rated parental involvement as an urgent aspect of elementary school education. The study discovered no significant difference between male and female students, significant differences among sophomore, junior, and senior students, and significant differences among students of public and private higher education institutions. The findings indicated that all respondents agreed on the importance of involvement and revealed implications for the elementary education study program.